FUNGSI PEMBINAAN NARAPIDANA PENERIMA PEMBEBASAN BERSYARAT DI LAPAS PEREMPUAN KELAS III JAYAPURA, KEEROM - april, Dwi Aprilia (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
This study discusses the coaching function carried out in the Class III women’s correctional instistution  in keerom in order to integrate inmates after returning to society. The implementation of prisoner coaching is a government program regulated in the Correctional Law by stipulating two types of coaching, namely personality development and independence development. The implementation of this coaching each  has a different goal in fostering inmates. This research focuses on the implementation of the development  of assisted residents towards the granting of parole.The type of research used was qualitative descriptive where interviews were conducted in depth with related parties  through a sociological juridical approach. The technique of data collection and data management used observation, interview, and documentation methods for the results of inmate coaching in the Class III women’s correctional  institution in Keerom. The results of this study will sho that the more effective the development of inmates will create positive values that grow the quality of the inmates themselves so that changes occur in order to prevent criminal behavior when they are successfully relased. The change in the last Correctional law is a function to further maximize the correctional system, namely humanizing humans by applying the development  of independence and personality and supported by facilities and infrastructure in the process of implementing inmate coaching so that the coaching runs with is expected by the government and the community.